Estimating the acute impacts of Arctic marine oil spills using expert elicitation. (June 2018) - Nevalainen, Maisa; Helle, Inari; Vanhatalo, Jarno
Abstract: Increasing maritime traffic in the Arctic has heightened the oil spill-related risks in this highly sensitive environment. To quantitatively assess these risks, we need knowledge about both the vulnerability and sensitivity of the key Arctic functional groups that may be affected by spilled oil. However, in the Arctic these data are typically scarce or lacking altogether. To compensate for this limited data availability, we propose the use of a probabilistic expert elicitation methodology, which we apply to seals, anatids, and seabirds. Our results suggest that the impacts of oil vary between functional groups, seasons, and oil types. Overall, the impacts are least for seals and greatest for anatids. Offspring seem to be more sensitive than adults, the impact is greatest in spring, and medium and heavy oils are the most harmful oil types. The elicitation process worked well, yet finding enough skilled and motivated experts proved to be difficult. Highlights: We use elicitation to assess the vulnerability and sensitivity of Arctic biota to oil. Probability distributions are used to express the uncertainty (of the estimates). Medium and heavy oils are the most harmful for Arctic seals, anatids, and seabirds. Seasonality should be taken into account in Arctic oil spill risk assessments.